Developing a Project of an Integrated Supply Chain Planning and Establishment of Budgeting - Tatyana K.Miroshnikova; Valentina I. Epifanova; Andrey V. Kharlamov (International Journal of Supply Chain Management, 2019)
The main goal of this research is consists in development of the project of complex statement of a budgeting system on small business by considering the supply chain management. It is used systemically - process approach to statement of a budgeting system, an integrated approach to formation of financial and budgetary structures, the analytical approach assuming specification of categories and allocation of basic elements of model of process of budgeting of small enterprises. The integrated approach to management including formation of financial structure on the basis of organizational structure, determination of the budgetary structure and existence of result from modeling of elements of process. The technique of complex statement of budgeting of small enterprises is developed for realization of long-term supply chain strategy. The project of complex statement of budgeting can act as the fundamental tool in management of development by the small business representing the indicator of actual state for monitoring and adoption of effective management decisions.